2000
DOI: 10.1039/b002138p
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of tertiary amphetamines with 9-fluorenylmethyl chloroformate for liquid chromatography: determination of N-methylephedrine

Abstract: The fluorogenic reagent 9-fluorenylmethyl chloroformate (FMOC) was evaluated for the derivatization of tertiary amphetamines prior to liquid chromatographic analysis. Conditions for the derivatization were investigated, including the reaction time, the derivatization reagent concentration and the pH, using N-methylephedrine as a model compound. On the basis of these studies, a method for the quantification of N-methylephedrine is presented. The method involves derivatization with FMOC at ambient temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Another study has reported the derivatization of mulberry sample by using 9-fluorenylmethyl chloroformate, which reacts with primary and secondary amines under mild conditions producing DNJ derivatives. However, the reaction of 9-fluorenylmethyl chloroformate with tertiary amines requires dealkylation [68,69].…”
Section: 1-deoxynojirimycinmentioning
confidence: 99%
“…Another study has reported the derivatization of mulberry sample by using 9-fluorenylmethyl chloroformate, which reacts with primary and secondary amines under mild conditions producing DNJ derivatives. However, the reaction of 9-fluorenylmethyl chloroformate with tertiary amines requires dealkylation [68,69].…”
Section: 1-deoxynojirimycinmentioning
confidence: 99%
“…1, the dealkylation of the initially formed TMA-FMOC derivative (Rxn 1) can yield an identical FMOC derivative product (Rxn 2) as DMA (Rxn 3). 24,30 However, the dealkylation of the TMA-FMOC acylammonium salt is slow at room temperature and hence the DMA-FMOC carbamate product is insignicant. As a result TMA is detected as an acyl ammonium salt and eluted before the carbamates of MA and DMA.…”
Section: The Products Of Amine-fmoc Derivatization Reactionmentioning
confidence: 99%
“…Short chained aliphatic amines (e.g., methylamine (MA), dimethylamine (DMA), and trimethylamine (TMA)) are well known for their potential in the formation of secondary organic aerosols. 1,2 Moreover, they are widely publicized malodorants (pungent, rotten-sh like smell) with low odor threshold values (in the range of [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], and 0.032-0.21 ppb (v/v), respectively for MA, DMA, and TMA). 3 Amines in the presence of nitrogen oxides or other nitrosating agents can easily form N-nitrosamines which can pose potential health hazards as mutagens and carcinogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit of detection and quantification were 0.1 and 0.5 µg/ml, respectively. 10) Simple and rapid determination of APs and ephedrines with diode array detection was performed using solid-phase extraction. The recovery rates were at least 85%.…”
Section: )mentioning
confidence: 99%